An indirect online method for measuring the boiling rate of BFG boiler economizer. (February 2020) - Ye, Yalan; Wang, Hongming; An, Xiang
Abstract: In blast furnace gas (BFG) boiler, high flow and large velocity of the flue gas will cause more heat to be absorbed by tail heating surfaces such as economizers. This will increase the probability of water boiling and vaporizing in economizer, which may cause safety accidents. Therefore, to facilitate the safe operation of boilers, it is of vital importance to grasp the boiling rate of economizer in real time. However, due to the complex state of medium in the piping, it is difficult to measure the boiling rate of economizer directly. Aiming at this issue, this paper presents an indirect online method for measuring the boiling rate of BFG boiler economizer through boiler operation parameters, based on heat transfer balance calculation. In this method, the boiling rate of economizer can be obtained indirectly through the boiler operation parameters on flue gas side and steam–water side. The measuring result can be used as the basis for boiler operation and adjustment, thus make the economizer running in a safe state for a long time, which can prolong the operation life of economizer.